Understanding the Impacts of Financial Flows in the Landscape - Louman, B.; Shames, S.; Pamerneckyte, G.; Owusu Ansah, M.; Koesoetjahjo, I.; Nghi, T.H.; Kusters, K. (MDPI, 2021)
Donors and non-governmental organizations are showing increased interest in integrated landscape initiatives (ILIs), where landscape stakeholders work together to achieve common goals related to development, climate change and conservation. In order to support the work of ILIs, we developed a novel methodology with which stakeholders—organized in multi-stakeholder partnerships—can assess how financial flows in the landscape are impacting their common goals and to identify funding gaps. Piloting the methodology in three landscapes in Indonesia, Ghana and Vietnam, we found that there were trade-offs between ensuring broad stakeholder participation in the assessments (to capture different perspectives) and the level of technical and quantifiable detail that could be acquired. The methodology effectively contributed to a common understanding among landscape-level stakeholders and triggered discussions on methods in which financial flows can be adapted to reduce their negative impacts or increase their positive impacts. It also functioned as a basis for the development of joint action plans and to initiate collaborations with the providers of financial flows that have potential to contribute to common landscape objectives. In addition to promoting common understanding and providing a basis for the development of action plans, we conclude that implementing the methodology also helped with strengthening the landscape partnerships themselves.